All-Suture Anchor Techniques for Biceps Tenodesis Are Noninferior in End-Cycle Stiffness to an Interference Screw Technique; However, Secondary Outcomes, Such as Ultimate Failure Load, Yield Load, Creep, and Load-to-Failure Stiffness, Are Inferior in an Ovine Model - Kendal Carter, M.D.; Emily Rogers, B.S.; Nicholas J. Peterman, B.S.; Vincent Wang, Ph.D.; John R. Tuttle, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To assess the biomechanical performance of 2 simplified loop-and-tack biceps tenodesis techniques, all-suture anchor and all-suture anchor with a button, compared with the interference screw technique in an ovine model. Methods: Twenty-one biceps tenodesis procedures were executed on the humeri and flexor digitorum profundus tendons of skeletally mature, female sheep. Limbs were evenly randomized into 2 experimental groups (all-suture anchor with or without button) and 1 control group (interference screw). Cyclic loading followed by a load-to-failure test was conducted. The primary outcome metric was end-cycle stiffness, or stiffness measured at the end of cyclic loading, because it modeled the resistance of the construct to the lower-force activities of postoperative physical therapy. Secondary metrics included ultimate failure load (UFL), yield load, creep, and load-to-failure stiffness. End-cycle stiffness difference-of-means testing was conducted with a minimal clinically important difference threshold of –15 N/mm (–1.5 kg/mm). Groups were compared using analysis of variance for all recorded variables. Results: Both the all-suture anchor techniques, without a button and with a button, were found to be noninferior in end-cycle stiffness to the interference screw technique (–5.2 N/mm [95% confidence interval, –13.6 to 3.3 N/mm] and –3.8 N/mm [95% confidence interval, –12.5 to –4.9 N/mm], respectively) with a minimal clinically important difference of –15 N/mm. The all-suture techniques showed significantly lower UFL, lower yield load, greater creep, and lower load-to-failure stiffness (P < .001, P < .001, P = .002, and P < .001, respectively). Tendon dimensions did not vary significantly across groups. Conclusions: Under subfailure loading conditions, the all-suture anchor techniques with a button and without a button showed end-cycle stiffness noninferiority to an interference screw technique; however, these techniques were inferior in all secondary outcomes, including significantly lower UFL, lower yield load, greater creep, and lower load-to-failure stiffness. Clinical Relevance: The all-suture anchor approaches with a button and without a button may retain the natural length-tension dynamics of the long head of the biceps tendon because fixation can occur before the release of the tendon origin. Additionally, they may offer a simpler and more cost-effective alternative to prevailing arthroscopic methods.